Marked colour divergence in gliding membranes of a tropical lizard mirror population differences in the colour of falling leaves - Klomp, D.A.; Stuart-Fox, D.; Das, I.; Ord, T.J (The Royal Society, 2014)
Populations of the Bornean gliding lizard, Draco cornutus, differ markedly in the colour of their gliding membranes. They also differ in local vegetation type (mangrove forest versus lowland rainforest) and consequently, the colour of falling leaves (red and brown/black in mangrove versus green, brown and black in rainforest). We show that the gliding membranes of these lizards closely match the colours of freshly fallen leaves in the local habitat as they appear to the visual system of birds (their probable predators). Furthermore, gliding membranes more closely resembled colours of local fallen leaves than standing foliage or fallen leaves in the other population’s habitat. This suggests that the two populations have diverged in gliding membrane coloration to match the colours of their local falling leaves, and that mimicking falling leaves is an adaptation that functions to reduce predation by birds.